Investigation on slope stability using monte carlo simulation: A case study of ULU jelai hydroelectric project - Nurul Umibaiti A.R. (Springer, 2023)
Dams; Decision making; Intelligent systems; Monte Carlo methods; Probability distributions; Safety factor; Slope protection; Deterministic design; Factor of safety; Geotechnical investigations; Ground parameters; Highway; Hydroelectric project; Long-term maintenances; Probabilistic approaches; Slope stability